Critical incident sparks critical incident sparks critical incident: an 'aresolutionist' method. Issue 3 (4th May 2018) - Crowhurst, Michael; Patrick, Rachel
Abstract: In this article the authors propose a concept of a resolutionism and outline an a resolutionist method/ology which emerged from reflective practice research. This research was prompted by an event that occurred during a tutorial and the outlined methodology is illustrated by an account of subsequent events and processes. The authors draw on poststructuralist theorizing and methods such as writing as inquiry to counter the resolutionism that permeates dominant approaches to research and reflective practice. In their own research, the authors' aim shifted from solving a pedagogic problem to analyzing the event as a complex assemblage and exploring the discourses that circled their discussions about the event. A problem to solve had become an object of curiosity.